ADAPTING LANGUAGE LESSONS PLANS AND MATERIALS FOR FUTURE TOURISM PROFESSIONALS - Khamitov , Eldorbek (Mental Enlightenment Scientific-Methodological Journal, 2025)
Instructing English to prospective tourism professionals necessitates tailored modifications to address the linguistic and practical requirements of students in the travel and hospitality industries [3, pp-29]. This article examines the difficulties instructors encounter while utilizing authentic content, such as industry-specific articles, in the classroom. Factors like linguistic complexity [1], content relevance [4], student involvement, and skill integration are analyzed. The article outlines techniques for addressing these problems, such as pre-teaching vocabulary, curating pertinent content, and creating multi-skill activities that enhance engagement and facilitate practical language application [2]. These tactics are exemplified through a sample lesson plan designed for tourism professionals.